Wireless power transfer characteristics observations using inductive coupling method - Muse, Ibrahim Hersi (2021)
The purpose of this project is designing and modelling of a system for WPT using inductive coupling to eliminate the use of wires. In this project the problem of using the wires which will reduce the efficiency of the system will be eliminated. There are many ways to overcome the energy that will be dissipated in the wires of the wired systems, and here in this project will model one of those techniques which is inductive coupling. This method will help to transfer the power wirelessly and the use of the wires will be eliminated, but with less distances. This project will give information that the power is transferred wirelessly and the distance effect for the output power of the WPT. Still some of the low power devices need a developed procedure for safe and accurate wireless power transfer. So this project will highlight some aspects for wireless power transfer. By using math lab Simulink maximum efficiency was achieved while the coupling coefficient K was 1 which is 97.33% in both theoretical and simulation results.